Joint Path and Spectrum Diversity in Cognitive Radio Ad-hoc Networks - Rahman, Md. Arafatur; Caleffi, Marcello; Paura, Luigi (Springer International Publishing AG, 2012)
The uncertain availability of the spectral resource imposes unique challenges in cognitive radio networks. One of the critical issues is to counteract the performance degradation experienced by cognitive users (CUs) due to the activity of primary users (PUs). Since the activity of PUs varies both in frequency and space domain, diversity techniques can represent an efficient way to address this issue. In this article, it is proposed to jointly exploit path and spectrum diversity for effective use of spectrum in cognitive radio ad-hoc networks (CRAHNs). By jointly exploiting both the diversities, CUs can switch dynamically to different paths and spectrum bands for communicating with each other in presence of frequency- and space-varying PU activity. This idea is adopted in a routing protocol, referred to as Dual Diversity Cognitive Ad-hoc Routing Protocol, and simulation results reveal the effectiveness of introducing joint path and spectrum diversity in CRAHNs.